2013
DOI: 10.1016/j.cardfail.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual Assessment of Brain Magnetic Resonance Imaging Detects Injury to Cognitive Regulatory Sites in Patients With Heart Failure

Abstract: Background Heart failure (HF) patients exhibit depressive and executive function impairments that contribute to HF mortality. Using specialized magnetic resonance imaging (MRI) analysis procedures, brain changes appear in areas regulating these functions (mammillary bodies, hippocampi, and frontal cortex). However, specialized MRI procedures are not part of standard clinical assessment for HF (which is usually a visual evaluation), and it is unclear whether visual examination can detect changes in these struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
(52 reference statements)
2
26
0
Order By: Relevance
“…Because impaired cardiac function was reported to relate to the circulatory system (including cerebral perfusion), we consider that the ICD patients with impaired cardiac function also have CNS hypoperfusion, which is one of the causes of cerebral atrophy . In addition, previous magnetic resonance imaging studies have reported that the hippocampus, frontal cortex, and insular cortex were injured in patients with severe cardiac dysfunction . These reports concluded that brain hypoperfusion caused by impaired cardiac function was a critical factor resulting in temporal lobe and cerebral dysfunction.…”
Section: Discussionmentioning
confidence: 95%
“…Because impaired cardiac function was reported to relate to the circulatory system (including cerebral perfusion), we consider that the ICD patients with impaired cardiac function also have CNS hypoperfusion, which is one of the causes of cerebral atrophy . In addition, previous magnetic resonance imaging studies have reported that the hippocampus, frontal cortex, and insular cortex were injured in patients with severe cardiac dysfunction . These reports concluded that brain hypoperfusion caused by impaired cardiac function was a critical factor resulting in temporal lobe and cerebral dysfunction.…”
Section: Discussionmentioning
confidence: 95%
“…Although reports of hypoxia-ischaemia causing severe, and selective damage to the mammillary bodies are rare, extensive atrophy of this structure has been described in adults after prolonged heart failure (Kumar et al., 2009, Pan et al., 2013). Volume reduction in the medial nucleus of the mammillary bodies has also been reported following adult-onset damage to the hippocampus and fornix (Loftus et al., 2000, Schubert and Friede, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Possible pathophysiological mechanisms are associated with chronic cerebral hypoperfusion, microemboli from LV thrombi, disruptions of blood–brain barrier, vascular remodelling, systemic inflammation and endothelial dysfunction. Accordingly, injury and tissue loss of brain areas involved in cognition have been described such as in the frontal cortex, hippocampus, mammillary bodies, and the putamen . Clinical factors associated with cognitive decline and dementia in HF include a history of hypertension, stroke, AF, metabolic abnormalities, reduced ejection fraction and low cardiac output, impaired LV diastolic filling, high plasma brain natriuretic peptide, reduced physical activity, depression, anaemia, liver failure, increased homocysteine, and low testosterone levels in males …”
Section: B Higher Cortical Functionmentioning
confidence: 99%